EFECTO DE SUSTRATOS ORGÁNICOS EN LA GERMINACIÓN DE SEMILLAS DE GUANÁBANA (Annona muricata) EN SU DESARROLLO VEGETATIVO INICIAL - Ríos Sotomayor, Pedro Adrián (2023)
The plant produced in a nursery depends in part on the substrate where it develops, since it is where its root system is anchored and from there it obtains water and nutrients. The present study was carried out with the objective of evaluating the effect of different substrates. organics in the cultivation of soursop (Annona muricata L) in its initial development stage. The variables that were considered were: days to germination, germination percentage, plant height, diameter of the seedling, number of leaves, root length and survival percentage.